Metabolic and biochemical alterations in Alzheimer's disease: facts and fictions - Smith, Mark A. (Henry Stewart Talks, 2011)
What causes selective neuronal loss in AD?, Tauist and BAPtist hypothesis of AD, Pathology and oxidative stress relationship, NFT and amyloid-beta, Stress-activated protein kinases and phospho-tau, Amyloid-targeted approaches are unsuccessful, Amyloid-beta controls redox activity, Genetic factors are related to oxidative stress, Therapeutics, Potential mechanism of ROS generation, Oxidative modifications and macromolecules, Oxidative damage directly correlates with mtDNA, Abnormal mitochondrial distribution in AD brains, Iron histochemistry, Antioxidant diet is protective, Only one non-amyloid drug in phase III: 2010, Oxidative stress is necessary but not sufficient, CaMKII-MYC mice, Oxidative stress and cell cycle abnormalities, Early stages of AD disease signals